Visuo-Haptic Immersion Made Easy: A Fast-Track Course on Spatial Anchors - Ohara, David; Oliveira, Robson; Nunes, Fatima; Teixeira, João Marcelo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Mixed Reality (MR) occupies the midpoint of the Reality–Virtuality continuum, blending real and virtual elements into a unified environment, which can reach high levels of immersion by integrating spatial, visual, and haptic cues, preserving real-world awareness while convincingly embedding virtual content. A key driver of this experience is multisensory integration, where vision often dominates and shapes perceptions in other modalities, influencing tactile judgments and increasing the illusion of touch. To explore this visuo-haptic integration, we propose a tutorial that guides participants to design and implement a Meta Quest 3 application in Unity that harnesses Spatial Anchors to precisely align 3D models with physical objects. Through a combination of concise theoretical overviews and hands-on exercises—from environment scanning and anchor management to deployment—attendees will acquire practical skills to create, save, and interact with stable visuo-haptic experiences, leaving with a functional prototype and a clear development pipeline for Visuo-Haptic immersive applications.